Role ambiguity, role conflict and customer orientation behaviour : a look at life insurance industry in Malaysia / Nor Azila Mohd Noor and Azli Muhamad - Mohd Noor, Nor Azila; Muhamad, Azli (Institute of Quality and Knowledge Advancement (InQKA) and University Publication Centre (UPENA), 2007)
The study examines the role of managers in enhancing the quality of customer services among customer-contact personnel in life insurance industry. In the competitive environment of insurance industry, there is constant pressure to innovate and develop new ways to improve the quality of services to customers. One approach which has been emphasised by the Life Insurance Association of Malaysia is to encourage agents to adopt customer-orientation behaviour in their selling activities. Customer-orientation behavior is defined as the degree to which agents practice the marketing concept in their selling activities by trying to help their customers to make purchase decisions that will satisfy customers' needs. It involves the satisfaction of customer needs through the individual relationship between customer contact personnel (agent) and customers. In order to become customer-oriented, managers play an important role in supervising their agents. This study explores the importance of two role perception factors, which consists of role ambiguity and role conflict in enhancing customer-orientation behaviour of the agents. Data gathered from 445 life insurance agents were used to test the hypothesised relationships. The results supported the hypotheses that both role ambiguity and role conflict negatively affect agents to adopt customer-orientation behaviour in their selling activities. This justify that managers should play role in reducing agents from experiencing role ambiguity and role conflict in their jobs. The theoretical implications and managerial implications, particularly the important role of insurance managers in dealing with insurance agent's customer-orientation behaviour, of these findings are discussed.